KEBIJAKAN MENTERI DALAM NEGERI TENTANG PERSYARATAN PENGANGKATAN PENJABAT GUBERNUR DALAM PEMILIHAN KEPALA DAERAH - SAEFUL KHOLIK; C A R T O C A R T O (President University, 2017)
Local Leaders Election (LLE) In Unison is in the National Government's agenda, as set out in Constitution No. 10 of 2016 concerning the second amendment to Law No. 1 of 2015 Concerning Determination of Government Regulation in Lieu of Law No. 1 of 2014 Regarding the LLE of Governors, Regents, and Mayors into Law. LLE in wave 3 (three) carried on June 27, 2018 one of them in the province of West Java. The tenure of the Governor and the Vice Governor of West Java exhausted before the inauguration of Governor election so requires for the Acting Governor to fill the vacancy (vacuum of power). Acting Governor of West Java charging filled by Police Commissioner General M. Iriawan is active Police who took office Main Secretary National Security Institution, which became the basis of the appointment of Act No. 5 of 2014 concerning the State Civil Apparatus and Government Ordinance No. 4 of 2002 on the Amendment of the GO 15 of 2001 on Transfer of Status of the National Army of Indonesia and the Indonesian National Police Members. This study aims to determine (1) Does the Police General Appointment as Acting Governor Active berdsarkan meet the requirements Perturan legislation. (2) How Legal Implications of the Establishment of the Acting Governorof the Police General active status. From these results it can be concluded that: (1) Terms of the Acting Governor divided into 2 (two). First, its main base is being Served in High Leadership Associate. Second, the addition of its situational namely the Police can fill positions in institutions Center for one of the agencies' Center which can be occupied by the Police is the National Security Institution or have a list value of execution of work for three (3) In the last at least have a good value , (2) Implications that can arise as a result of the appointment of the Active Police General as Acting Governor are substantially possible for electoral legal implications, especially related to the Political aspect, including a tendency or concern to cause non-marginalization because there are regional election participants from the Police Agency.